The Fascinating Connection between Neuroscience and Mathematical Learning (Docentes 2.0 Journal, 2025)
Neuroscience studies the nervous system and brain, offering valuable insights into how mathematics is learned and taught. This study aimed to analyze which brain regions are activated and how they relate to mathematical learning, brain plasticity, and the impact of emotional factors on mathematical connections. The research employed a systematic methodology, a qualitative approach, and a naturalistic paradigm. It used a topical narrative design, focusing on a single topic, and a bibliographic documentary approach, drawing on existing documentary sources. The databases were Scopus, ScienceDirect, EBSCO, Web of Science, and ProQuest; the PRISMA 2020 method was applied. The articles found were mostly in English, published between 2020 and 2024, and were available for open access. Eighteen publications were finalized for analysis. Key findings include cortical anatomy, early mathematical skills, and the activation of brain regions in the frontal, intraparietal, and temporal areas. The research highlights the relevance of neuroscience in mathematics learning. It delves into the importance of brain plasticity, the activation of specific brain areas, and emotional factors in the educational process. It emphasizes the need to incorporate neuroscientific discoveries into pedagogical practice to improve the teaching and learning of mathematics. It also emphasizes understanding subjective experiences and using playful strategies to learn mathematics.
Keywords: Neuroscience; neuroeducation; emotions; mathematical learning; brain plasticity